GENETIC COMMUNICATIONS IN SYSTEM “PARASITE-OWNER” - Помогайбо, В.М.; Петрушов, А.В. (World of Medicine and Biology, 2015)
Genetic communications (horizontal transfer of genes, lateral transfer of genes) consist of transfer by organism its genes to other organism which isn’t his descendant. This phenomenon is possible not only between organisms of allied species, but also between organisms of different highest taxons and even kingdoms – bacteria and protozoa, bacteria and nematodes, mushrooms and insects, plants and mushrooms, protozoa, insects. The Horizontal Transfer of Genes (HTG) – the all-biological phenome-non and a source of fast and mass variability of organisms without mutations and recombinations. It is carried out in three ways: by means of vectors (virus-es, plasmids, mobile genetic elements), on condition of close physical contact (copulation, conjugation, symbiosis, commensalism, parasitism, transplanta-tion), and also by means of parasites couriers. HTG doesn’t demand partners’ presence at the same time in a certain place, but close physical contact between them increases its probability. However the fact of movement of a certain gene won’t provide its expression in a new genome yet. For this purpose it has to be integrated into a new genome, and its functioning has to answer features of a recipient organism. HTG is extremely widespread among procaryote. Ability of bacteria quickly use new living conditions and the easiness with which some their types gain resistance to the whole range of antibiotics, are possible only under condi-tion if these properties extend within species, but aren’t generated by each line of bacteria independently. In the process of increase in sequenced genomes quantity of eucaryotes appears more and more data which testifies bout preva-lence of HTG among organisms of all levels of the organization, including mushrooms, plants, animal and even the human being. So far the most powerful proof of HTG implementation between certain types of organisms remains the DNA sequenation. Different organisms consid-erably differ according to the general maintenance of certain bases in DNA molecule, on features of use of different triplets for coding of the same amino acids, on frequencies of repetitions, etc. It gives the chance to identify poten-tially alien genes on their atypical nucleotide structure or on deviations in use of codons. However for strong evidence the molecular-genetic HTG data aren’t enough. Results of a sequenation of genomes have to be confirmed with mor-phological, physiological, ecological and biogeographical researches. Parasites exist in organism of the owner or on it, trophic depend on it and therefore have long physical contact with it. This condition provides con-siderable opportunities for an exchange of genetic material between a parasite and the owner. However, mechanisms of this phenomenon in most cases re-main unknown though it is revealed that DNA is more resistant to destruction, than was considered earlier. The part of it is capable to pass safely through gastrointestinal tract of an animal and on the blood course to reach practically any tissue of a body, including gametic. In system "parasite – owner" genetic communications are carried out in both directions. In this case the acquired genes can provide to recipient adapta-tion advantages – strengthening of virulence, ability to neutralize toxins, to re-sist to immune system of the owner, to utilize more successfully structures of his organism, etc. The majority of these properties the parasitizing eucaryotes get from the simbiont – bacteria and mushrooms. Sometimes the genes ac-quired by owner from parasite provide him incensement of the protective op-portunities. In systems "parasite – owner" evolves not each element in itself, but all system as a unit. The subsequent studying of these systems will provide the best understanding of processes of a genomic coevolution and parasitic epide-miology.